ANALISIS KEMAMPUAN LITERASI SISWA SMP DALAM MENYELESAIKAN SOAL MODEL PISA: FORMULATE DAN EMPLOY - Fidiyah Rachmah; Soffil Widadah; Nurina Ayuningtyas (JEDMA Jurnal Edukasi Matematika, 2023)
The study aims to describe students' mathematical literacy skills in solving PISA model problems, using qualitative methods with approaches to explore and understand a symptom by asking respondents questions, and analyzing data to draw conclusions. The subjects in the study consisted of 3 15-year-old junior high school students with criteria of high, medium and low math ability. The instruments in this study are tests and interviews. The results of this study concluded that students are highly mathematically capable and have good mathematical literacy skills, namely students are able to solve problems appropriately but have not met interpret indicators. Students with low mathematical ability cannot solve problems correctly and have not met all indicators on aspects of mathematical processes, meeting only two aspects of mathematical processes, namely formulate and employ.